Sofistas e filósofos como rectores urbis: espaço, identidade e ordem pública nos discursos cívicos de Dion de Prusa (sécs. I-II) - Erlacher, Esdra (2023)
In this dissertation, we propose to discuss the political performance of the sophist and philosopher Dion de Prusa as an instructor of eastern urban communities, in the 1st and 2nd centuries. In the first centuries of the Christian Era, the Greek city, the main scene of the author's performance, was a space for disputes over power and the affirmation of identities, because of the context of Roman domination. Given this scenario, our focus of study is to analyze the way in which Dion de Prusa educates the inhabitants of the poleis of Rhodes, Alexandria, Nicaea, Nicomedia, Tarsus and Apamea. In this sense, the city is the main aspect mobilized by the author in his civic prayers. Based on these ideas, we could infer the central hypothesis of this work: Dion de Prusa, in his civic prayers, instructed urban communities with the purpose of integrating them into the Roman imperial order, which characterized his political action in the context of Roman domination over the póleis. In addition, the author's representation of the ideal pólis has urban space as its stand, insofar as the good use of the built environment is used as an element capable of evoke pride in citizens, while the bad use must be corrected. As a theoretical contribution we use the concepts of Representation, by Roger Chartier (1990), Identity, according to Tomaz Tadeu da Silva (2004), Space, according to Navarro (2007), City, as proposed by Lacaze (1999) and Public Order, according to Vergottini (2000). As a methodology for the treatment of sources, we use Content Analysis, as proposed by Laurence Bardin (2011).